Optical fiber mercury biosensor based on immobilized urease and bromothymol blue onto the alginate-chitosan membrane in the flow-system - Dhony Hermanto; Mudasir; Dwi Siswanta; Bambang Kuswandi; Nurul Ismillayli (Kuwait Journal of Science)
An optical fiber biosensor has been developed for detection of Hg(II) ion based on inhibition of urease immobilized onto alginate–chitosan membrane, coupled with bromothymol blue (BTB) in the flow-system. In order to get good performance of the biosensor toward Hg(II) ion detection, the experimental parameters of the biosensor were optimized. Here, the biosensor showed maximum wavelength at 580 nm, with the optimum pH at 6. The calibration curve had a dynamic working range at 10 to 500 µg/L of Hg(II) ion with a detection limit of 12.1 µg/L (equal to 10% inhibition) and highly reproducible (RSD= 0.86%). The regeneration of the biosensor has been performed by treating with 1 mM ethylenediaminetetraacetic acid (EDTA) solution where up to 5 times cycles have been achieved with the inhibition decrease to 9.94% from the original biosensor response. Applying the biosensors to real samples showed the conformity of results with the reference method, cold vapor-atomic absorption spectrometry (CV-AAS).